2020
DOI: 10.1021/acs.est.0c05052
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Zerovalent Iron (Fe0) and Microbiological Trichloroethene and Perchlorate Reductions Are Determined by the Concentration and Speciation of Fe

Abstract: Trichloroethene (TCE) and perchlorate (ClO4 –) are cocontaminants at multiple Superfund sites. Fe0 is often used during TCE bioremediation with Dehalococcoides mccartyi to establish anoxic conditions in the aquifer. However, the synergy between Fe0 abiotic reactions and microbiological TCE and ClO4 – reductions is poorly understood and seldom addressed in the literature. Here, we investigated the effects of Fe0 and its oxidation product, Fe2 +, at field-relevant concentrations in promoting microbial TCE and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…Tempe and Bozeman soils were collected using a hand trowel from a depth of 0.2–0.4 m below the ground surface. Lucas soil was excavated from a depth of 1.5 m. Goodyear soil was acquired through drill coring from a depth of 25–52 m below ground surface [ 27 ]. Equal parts of ~0.1 kg of soil cores from 25–52 m depths were homogenized to create composite Goodyear soil.…”
Section: Methodsmentioning
confidence: 99%
“…Tempe and Bozeman soils were collected using a hand trowel from a depth of 0.2–0.4 m below the ground surface. Lucas soil was excavated from a depth of 1.5 m. Goodyear soil was acquired through drill coring from a depth of 25–52 m below ground surface [ 27 ]. Equal parts of ~0.1 kg of soil cores from 25–52 m depths were homogenized to create composite Goodyear soil.…”
Section: Methodsmentioning
confidence: 99%
“…Three groundwater samples were obtained for testing. One groundwater sample was from Phoenix Goodyear Airport-North Superfund site (AZ) (Rangan et al , 2020 ). The other samples were collected from two confidential sites in the Southwestern United States.…”
Section: Methodsmentioning
confidence: 99%
“…The developed IC method was applied to monitor anions in soil and culture-only batch microcosms. Soil laboratory microcosms (Ziv-El et al , 2011 ; Rangan et al , 2020 ; Joshi et al , 2021 ) focused on abiotic and microbiological Cr (VI) reduction were established in 160 mL glass serum bottles with 25 g of Cr (VI)-contaminated soil and 100 mL anaerobic mineral medium as described elsewhere (Delgado et al , 2012 , 2017 ). The soil was collected from 0 to 0.25 m depth at the TCCL site, India, and was homogenized in the anaerobic glove chamber (Coy Laboratory Products, Inc., Grass Lake, MI) under 3.5% H 2 and 96.5% N 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such insight is crucial to understand the potential synergy between nano-and bioremediation by determining, for example, if nZVI may have a biostimulatory effect on microorganisms participating in bioremediation. High Fe 0 concentrations (16.5 g/L) were deposited in both a sampled soil and groundwater contaminated by TCE and ClO4 -, preliminarily bioaugmented with dechlorinating microorganisms (Rangan et al, 2020). It was observed that the particles promoted TCE abiotic reduction to ethene and ethane, while impairing microbiological TCE and ClO4reduction.…”
Section: Potential Adverse Effects On Microbiotamentioning
confidence: 99%